Adrenal insufficiency, be aware of drug interactions! - Elke Thijs; Katrien Wierckx; Stefaan Vandecasteele; Annick Van den Bruel (Endocrinology, Diabetes & Metabolism Case Reports, 2019)
A 42-year-old man with complaints of muscle soreness and an increased pigmentation of the skin was referred because of a suspicion of adrenal insufficiency. His adrenocorticotropic hormone and cortisol levels indicated a primary adrenal insufficiency (PAI) and treatment with hydrocortisone and fludrocortisone was initiated. An etiological workup, including an assessment for anti-adrenal antibodies, very long-chain fatty acids, 17-OH progesterone levels and catecholamine secretion, showed no abnormalities. 18Fluorodeoxyglucose positron emission tomography/CT showed bilateral enlargement of the adrenal glands and bilateral presence of an adrenal nodule, with 18fluorodeoxyglucose accumulation. A positive tuberculin test and positive family history of tuberculosis were found, and tuberculostatic drugs were initiated. During the treatment with the tuberculostatic drugs the patient again developed complaints of adrenal insufficiency, due to insufficient dosage of hydrocortisone because of increased metabolism of hydrocortisone.